The Value of Javanese Philosophy in Society as a Form of Mass Communication in the Context of the Implementation Element of Covid 19 Handling and SDGs - Endro Tri Susdarwono (Jurnal Ilmiah Komunikasi Makna, 2020)
The purpose of this study is to raise the values that exist in the main Javanese philosophy which is communicated by the masses in the roots of society as the capital of implementing Covid 19 and SDGs. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. Channels of mass communication in instilling the values of Javanese philosophy into the roots of society through a variety of channels, one of which is able to attract the masses through puppet performances. The meaning behind the puppet show is a spectacle that serves as entertainment as well as being a picture and guide of life. Other channels which are a process of mass communication are also found in both written and unwritten teachings. Javanese philosophical values embedded in the roots of the community are valuable capital used in the implementation of covid 19 management and implementation of SDGs because these values are very appropriate and have long rooted in the practice of people's daily lives. Only a policy is needed to revive the values of Javanese philosophy so that it can be implemented as a covid handler 19 policy and SDGs implementation.